24 January 2020 Sivrice-Elazig, Turkey earthquake: geotechnical evaluation and performance of structures - Sayin, Erkut; Yon, Burak; Onat, Onur; Gor, Mesut; Oncu, Mehmet Emin; Tugrul Tunc, Esra; Calayir, Yusuf (Springer, 2021)
The January 24, 2020 Sivrice-Elazig (Mw = 6.8) earthquake occurred on the East Anatolian Fault zone. Main shock of this earthquake was occurred 20:55 at local time. The Peak Ground Acceleration was equal to 0.3 g at the epicenter (Sivrice district) of the earthquake. Even though the main shock was moderate, its effects on the structures were rather serious. The main shock caused significant damage and resulted in 41 casualties. 1540 buildings were damaged moderately, while 8519 buildings were damaged heavily and collapsed. This main shock effected four cities surrounded the epicenter due to its shallow earthquakes. The purpose of this paper is to summarize past and present seismic characteristics of the earthquake region. In addition, the aim of this paper is to summarize the seismotectonic of the region, the general characteristics of the earthquake and more specifically to report on the structural damage, and structural damage caused by the earthquake, observed during the site investigation. The damages were classified for reinforced concrete structures, masonry dwellings and non-residential structures. All distinguished earthquake induced failures and damages were discussed. Moreover, lessons learned were presented in this study.
Keywords: 2020 Sivrice-Elazı ğ earthquake; Seismotectonic features; Geotechnical effect; Reinforced concrete structures; Masonry dwelling; Structural failure